A Case of Ancient Bladder Stones from Oluz Höyük, Amasya, Turkey. (17th October 2013) - Özdemir, K.; Akyol, A. A.; Erdal, Y. S.
Abstract: A biological object was recovered from the pelvic region of an adult woman coded to SK13 unearthed from Oluz Höyük in Amasya, Turkey. The skeleton was dated to the medieval period on the basis of the burial customs and the calibrated 14 C dates. The find was identified as a bladder stone on morphological, radiographic and chemo‐analytical grounds with the help of X‐ray diffraction, polarised energy dispersive X‐ray fluorescence spectroscopy, confocal Raman spectroscopy, and microscopic techniques. The mineralogical composition of urinary stone was found to be as calcium phosphate (apatite). Bladder stone disease is endemic in poor agricultural regions where the typical diet is mostly based on grain carbohydrate consumption with scarce intake of animal protein. Copyright © 2013 John Wiley & Sons, Ltd.